2005
DOI: 10.1007/s10822-005-9002-6
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate docking: structure-based virtual screening at high throughput speed

Abstract: Structure-based screening using fully flexible docking is still too slow for large molecular libraries. High quality docking of a million molecule library can take days even on a cluster with hundreds of CPUs. This performance issue prohibits the use of fully flexible docking in the design of large combinatorial libraries. We have developed a fast structure-based screening method, which utilizes docking of a limited number of compounds to build a 2D QSAR model used to rapidly score the rest of the database. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 34 publications
0
28
1
Order By: Relevance
“…In preceding investigations it was shown that the use of the Bayesian classifiers trained on docking scores of experimentally known binders can be used for virtual screening [54][55][56][57]. In view of that, Filikov and coworkers also developed a surrogate docking method to pre-rank compounds to regular docking [58]. In this case the target protein was the cyclin-dependent kinase 2 (CDK2) and two sources of compounds were used: the NCI library and a combinatorial library composed by a set of 2,6,9-trisubstituted purines, a chemical family known to inhibit CDK2 as well as other kinases.…”
Section: Combined Ligand-based and Structure-based Vs Approachesmentioning
confidence: 99%
“…In preceding investigations it was shown that the use of the Bayesian classifiers trained on docking scores of experimentally known binders can be used for virtual screening [54][55][56][57]. In view of that, Filikov and coworkers also developed a surrogate docking method to pre-rank compounds to regular docking [58]. In this case the target protein was the cyclin-dependent kinase 2 (CDK2) and two sources of compounds were used: the NCI library and a combinatorial library composed by a set of 2,6,9-trisubstituted purines, a chemical family known to inhibit CDK2 as well as other kinases.…”
Section: Combined Ligand-based and Structure-based Vs Approachesmentioning
confidence: 99%
“…A similar concept of "surrogate docking" has been introduced recently by Filikov and co-workers [30]. They have developed a fast screening method, which utilizes docking of a limited number of compounds to build a 2D Quantitative Structure -Activity Relationships (QSAR) model used to rapidly score the rest of the database.…”
Section: Nb With Calculated Affinitiesmentioning
confidence: 99%
“…Treating explicitly the receptor flexibility is computationally expensive and could worsen the result [45], and hence would make this approach a less desirable method for high throughput virtual screening. Despite this recent methods such as fast structure-based screening [61], that utilizes docking and 2D QSAR for rapid scoring is reportedly thousand times faster than regular docking and still demonstrates a comparable performance [62][63][64][65][66][67][68].…”
Section: Structure-based Virtual Screeningmentioning
confidence: 99%